A Study on the Evaluation of Urban Tourism Competitiveness in Guangdong-Hong Kong-Macao Greater Bay Area. Issue 1 (June 2020) - Yang, Liang; Yu, Li
Abstract: Aiming at the shortcomings in the existing research on tourism competitiveness, the article adjusted the regional tourism competitiveness evaluation index system and used the entropy method to quantitatively evaluate the tourism competitiveness of 11 cities in the Guangdong-Hong Kong-Macao Greater Bay Area from 2012 to 2018. The results show that the regional tourism competitiveness of Guangdong-Hong Kong-Macao Greater Bay Area differs significantly and can be divided into three levels. Hong Kong, Macau, Guangzhou, and Shenzhen generally have higher tourism competitiveness and are in the first rank; Zhuhai, Foshan, Huizhou, and Dongguan have average tourism competitiveness and are in the second rank; The tourism competitiveness of Zhongshan, Jiangmen and Zhaoqing is relatively weak, ranking third. Based on the conclusions of the study, the article puts forward relevant suggestions to enhance the tourism competitiveness of the Guangdong-Hong Kong-Macao Greater Bay Area, hoping to provide a reference for enhancing the tourism competitiveness of the Guangdong-Hong Kong-Macao Greater Bay Area and promote the construction of international tourism destinations in the Guangdong-Hong Kong-Macao Greater Bay Area.